2010
DOI: 10.1002/mus.21762
|View full text |Cite
|
Sign up to set email alerts
|

Influence of stimulus pulse width on M‐waves, H‐reflexes, and torque during tetanic low‐intensity neuromuscular stimulation

Abstract: Neuromuscular electrical stimulation (NMES) has been shown to generate contractions that include a central recruitment of motoneurons; however, the effect of pulse width on electromyographic (EMG) and torque responses during NMES are not well documented. Soleus EMG and isometric plantarflexion torque were recorded from 14 subjects with NMES delivered to the tibial nerve using 50, 200, 500, and 1000 μs pulse widths. M-waves were significantly smaller during 20 Hz NMES compared with responses evoked by single pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 54 publications
(137 reference statements)
1
55
0
Order By: Relevance
“…Plausible reasons why previous studies of PAD in humans have not reported a similar depression of M-waves are that in some cases the amplitude of the second M-wave was not reported (Trimble et al 2000), stimulation frequencies above 5 Hz were not tested McNulty et al 2008), or trials were excluded if the M-wave amplitude changed more than 2% between pulses (Jeon et al 2007). A depression of M-wave amplitude during 20-Hz stimulation was recently reported when electrical stimulation was delivered using wide (500 and 1,000 s), but not narrow (50 and 200 s), pulse widths (Lagerquist and Collins 2010). This finding suggests that the M-wave depression stems from mechanisms related to the ability to repetitively activate motor axons beneath the stimulating electrodes, rather than reduced transmission across the neuromuscular junction or movement of the electrodes between pulses as a result of the muscle contraction.…”
Section: Discussionmentioning
confidence: 95%
“…Plausible reasons why previous studies of PAD in humans have not reported a similar depression of M-waves are that in some cases the amplitude of the second M-wave was not reported (Trimble et al 2000), stimulation frequencies above 5 Hz were not tested McNulty et al 2008), or trials were excluded if the M-wave amplitude changed more than 2% between pulses (Jeon et al 2007). A depression of M-wave amplitude during 20-Hz stimulation was recently reported when electrical stimulation was delivered using wide (500 and 1,000 s), but not narrow (50 and 200 s), pulse widths (Lagerquist and Collins 2010). This finding suggests that the M-wave depression stems from mechanisms related to the ability to repetitively activate motor axons beneath the stimulating electrodes, rather than reduced transmission across the neuromuscular junction or movement of the electrodes between pulses as a result of the muscle contraction.…”
Section: Discussionmentioning
confidence: 95%
“…Following NMES at 100 Hz, torque and H-reflexes were enhanced when using a 1-ms pulse duration, but not when using a 0.05-ms pulse duration (adapted from Collins 2010) et al 2011;Lagerquist and Collins 2010). Figure 4 shows that both H-reflexes and torque can be augmented after brief bursts of 100 Hz stimulation.…”
Section: Pulse Frequencymentioning
confidence: 85%
“…The sensory volley generated during NMES recruits motor units centrally in two distinct ways. Perhaps the most obvious form of central recruitment is through the Hoffmann-or H-reflex pathway Bergquist et al 2011;Lagerquist and Collins 2010). Like the M-wave, motor units recruited through H-reflex pathways discharge relatively synchronously although at a longer latency, as seen in the EMG traces in Fig.…”
Section: Nmes and The Central Recruitment Of Motor Unitsmentioning
confidence: 94%
See 1 more Smart Citation
“…First, the onset of tsDCS is accompanied by an initial itching sensation due to the activation of cutaneous afferents beneath the electrodes. Indeed, it has been shown that cranial (Delwaide and Crenna 1983;Ghanim et al 2009) and peripheral (Baldwin et al 2006;Klakowicz et al 2006;Lagerquist and Collins 2010) cutaneous stimulation may influence Sol H reflex (i.e., cutaneous effects might, by themselves, result in changes in spinal excitability). However, this possibility seems unlikely since 1) none of the subjects was able to differentiate active conditions from verum stimulation, and cutaneous perception has been shown to be similar between anodal and cathodal conditions (Ambrus et al 2011); 2) tsDCS-induced effects were specific to anodal polarity; and 3) spinal excitability was unchanged after both cathodal and sham stimulations.…”
Section: Discussionmentioning
confidence: 99%